Fluorescent Pteridine Derivatives as New Markers for the Characterization of Genuine Monofloral New Zealand Manuka (Leptospermum scoparium) Honey - Beitlich, Nicole; Lübken, Tilo; Kaiser, Martin; Ispiryan, Lilit; Speer, Karl (Journal of agricultural and food chemistry, 2016)
New Zealand manuka honey is well-known for its unique antibacterial activity. Due to its high price and limited availability, this honey is often subject to honey fraud. Two pteridine derivatives, 3,6,7-trimethyl-2,4(1H,3H)-pteridinedione and 6,7-dimethyl-2,4(1H,3H)-pteridinedione, have now been identified in New Zealand manuka honey. Their structures were elucidated by LC-QTOF-HRMS, NMR, and single-crystal X-ray diffraction after isolation via semipreparative HPLC. Their marker potential for authentic manuka honey was proved as both substances were detectable in neither the pollen-identical kanuka honey nor the nine other kinds of monofloral New Zealand honey analyzed (clover, forest, kamahi, pohutukawa, rata, rewarewa, tawari, thyme, and vipers bugloss). The fluorescence property of the pteridine derivatives can be used as an easy and fast TLC screening method for the authentication of genuine manuka honey. 6,7-Dimethyl-2,4(1H,3H)-pteridinedione has been described for the first time.